Nutrition and bariatric surgery [ - Kushner, Robert F. , 1953-; Still, Christopher D. (CRC Press, 2015)
"While bariatric surgery can lead to positive effects, it can also result in increased risk for nutrient malabsorption, deficiency, and clinical complications.This book addresses the dietary and nutritional care of the bariatric surgery patient. It explores the physiological changes that underlie selective nutrient malabsorption, preoperative nutritional assessment and dietary care of the patient through the surgery process, and nutritional clinical complications manifesting in anemia, neurological disorders, metabolic bone disease, and protein-calorie malnutrition. It also covers special populations, including adolescents and pregnant and lactating patients"--Provided by publisher